INTEGRASI KEARIFAN LOKAL DALAM PEMBELAJARAN DI SD N 2 KARANGLUHUR - Rahma Wulan Intan Nur’aini; Hania Kholifatul Lukmana; Nazilatul Atiqoh; Masna Nikmaturrohmah; Puji Rahayu; Nugroho Prasetya Adi (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
This study aims to describe the implementation of local wisdom in teaching at SD Negeri 2 Karangluhur, Kertek District, Wonosobo Regency. The research used a descriptive qualitative method with data collected through observations and interviews. The results indicate that the school has integrated local cultural values such as Lengger dance and the processing of carica fruit into thematic learning, particularly in IPAS and entrepreneurship subjects. These implementations are carried out through annual activities such as art performances and market day. The integration not only enhances students' understanding of local culture but also fosters creativity, learning enthusiasm, and character development that reflects love for culture and the surrounding environment. The findings suggest that local wisdom-based learning creates a contextual, enjoyable, and meaningful learning experience for elementary school students.